2017
DOI: 10.3389/fphar.2017.00559
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cooperation between KCa3.1 and TRPV4 Channels in Bronchial Smooth Muscle Cell Proliferation Associated with Chronic Asthma

Abstract: Airway smooth muscle cells (SMC) proliferation contributes to the airways remodeling and irreversible airway obstruction during severe asthma, but the mechanisms of airway SMC proliferation are poorly understood. Intracellular Ca2+ levels play an important role in regulating cell proliferation. We have previously reported KCa3.1 channels regulated human bronchial smooth muscle (HBSM) cells proliferation via the Ca2+ influx as a consequence of membrane hyperpolarization. However, the role of potassium channels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…It might be possible that the reduction of anion secretion also favour apical membrane hyperpolarization, a hypothesis that is supported by the more positive Vte recorded in the Kcnn4 -/-tissue that might be due to Na + accumulation in the mucosa and reduced anion secretion. Besides that, KCa3.1 inhibition has been widely proven by different groups to prevent or ameliorate several inflammatory events including those occurring in the airways (Girodet et al, 2013;Lin et al, 2015;Yu et al, 2017). Since our model is a systemic null-animal other might also participate in the reduction of inflammatory damage after Kcnn4 silencing.…”
Section: Discussionmentioning
confidence: 98%
“…It might be possible that the reduction of anion secretion also favour apical membrane hyperpolarization, a hypothesis that is supported by the more positive Vte recorded in the Kcnn4 -/-tissue that might be due to Na + accumulation in the mucosa and reduced anion secretion. Besides that, KCa3.1 inhibition has been widely proven by different groups to prevent or ameliorate several inflammatory events including those occurring in the airways (Girodet et al, 2013;Lin et al, 2015;Yu et al, 2017). Since our model is a systemic null-animal other might also participate in the reduction of inflammatory damage after Kcnn4 silencing.…”
Section: Discussionmentioning
confidence: 98%
“…It might be possible that the reduction of anion secretion also favored apical membrane hyperpolarization, a hypothesis that is supported by the more positive V te recorded in the Kcnn4 –/– tissue that might be due to Na + accumulation in the mucosa and reduced anion secretion. Besides that, KCa3.1 inhibition has been widely proven by different groups to prevent or ameliorate several inflammatory events, including those occurring in the airways ( 57 59 ). Since our model is a systemic null animal, other cells might also participate in the reduction of inflammatory damage after Kcnn4 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that blocking TRPV4 activity might be a strategy for scleroderma treatment ( Sharma et al, 2017 ). TRPV4 channels participate in the KCa3.1-regulated proliferation of human bronchial smooth muscle cells in the process of chronic asthma ( Yu et al, 2017 ), indicating that it is a potential therapeutic target for chronic asthma treatment. TRPV4 has also been determined to have a pathological role in the activation and proliferation of hepatic stellate cells ( Song et al, 2014 ; Zhan and Li, 2018 ), suggesting a potential therapeutic target for liver fibrosis treatment.…”
Section: Transient Receptor Potential Vanilloid 4 As a Potential Therapeutic Targetmentioning
confidence: 99%